Does short-term air pollution exposure have effects on blood pressure and heart rate in healthy women in the city of Niš, Serbia - Stanković, Aleksandra; Bogdanović, Dragan; Nikolić, Maja; Anđelković Apostolović, Marija (Central European Journal of Public Health, 2018)
OBJECTIVE: Epidemiological research has shown that air pollution is associated with cardiovascular events, but little is known about short-term effects on blood pressure (BP) and heart rate (HR) in Serbian population. The present study assessed the short-term association between black smoke (BS) and sulphur dioxide (SO2) levels in urban air and the daily values of blood pressure and heart rate in 98 healthy nonsmoking female volunteers. METHODS: Generalized regression model was fitted controlling for temperature, relative humidity, air pressure, season, and the day of the week. RESULTS: There was no association between short-term air pollution exposure and BP and HR, the exposure showed a tendency toward a decrease of diastolic BP and HR, but with no statistical significance. CONCLUSION: The present findings did not support the conclusion that current levels of ambient BS and SO2 may have an effect on blood pressure and heart rate in women.
Keywords: Cities; krevní tlak; Environmental Exposure; Female; velkoměsta; Humans; vystavení vlivu životního prostředí; kouř; Serbia; oxid siřičitý; Air Pollution; srdeční frekvence; Smoke; Srbsko; lidé; Sulfur Dioxide; ženské pohlaví; Blood Pressure; Heart Rate; časové faktory; znečištění ovzduší; Time Factors